How does buy service-based policy attract public transportation customers in Yogyakarta, Indonesia ? - Fitriani Fitriani; Achmad Nurmandi; Muhammad Lutfi; Mujizatullah Mujizatullah; Abu Muslim (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
The presence of public transportation (Trans Jogja and Friend Bus Jogja) is one of the solutions to overcome congestion and heavy traffic in Yogyakarta. However, in recent years, public transportation (Trans Jogja and Friend Bus Jogja) has had many problems, one of which is the lack of passenger numbers. It is because of these problems that occur in the field that the number of Trans Jogja passengers and Teman Bus Jogja is decreasing day by day. The purpose of this study is to find out the policies taken by the Yogyakarta Special Region government to increase and entice people to use public transportation. This study uses a qualitative descriptive analysis method that, as a whole, uses secondary data. This study found that there are four dimensions of service quality related to the Trans Jogja Minimum Service Standards: the tangibles dimension, the reliability dimension, the responsiveness dimension, and the assurance dimension. These four dimensions are running well and are in accordance with the applicable SPM, but these four dimensions need to be further improved. As for the factor that has reduced the interest of Trans Jogja users, namely the presence of online transportation services, Trans Jogja only operates at several predetermined points, and the operational time has also been determined. Unlike the case with online transportation, where online transportation is able to reach all areas in Yogyakarta and its operating hours are also flexible and in accordance with the wishes of prospective users.